A review on the recent progress, opportunities, and challenges of 4D printing and bioprinting in regenerative medicine. Issue 1 (2nd January 2023) - Pourmasoumi, Parvin; Moghaddam, Armaghan; Nemati Mahand, Saba; Heidari, Fatemeh; Salehi Moghaddam, Zahra; Arjmand, Mohammad; Kühnert, Ines; Kruppke, Benjamin; Wiesmann, Hans-Peter; Khonakdar, Hossein Ali
Abstract: Four-dimensional (4 D) printing is a novel emerging technology, which can be defined as the ability of 3 D printed materials to change their form and functions. The term 'time' is added to 3 D printing as the fourth dimension, in which materials can respond to a stimulus after finishing the manufacturing process. 4 D printing provides more versatility in terms of size, shape, and structure after printing the construct. Complex material programmability, multi-material printing, and precise structure design are the essential requirements of 4 D printing systems. The utilization of stimuli-responsive polymers has increasingly taken the place of cell traction force-dependent methods and manual folding, offering a more advanced technique to affect a construct's adjusted shape transformation. The present review highlights the concept of 4 D printing and the responsive bioinks used in 4 D printing, such as water-responsive, pH-responsive, thermo-responsive, and light-responsive materials used in tissue regeneration. Cell traction force methods are described as well. Finally, this paper aims to introduce the limitations and future trends of 4 D printing in biomedical applications based on selected key references from the last decade.